2017
DOI: 10.4274/balkanmedj.2015.1379
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Cases of Odontogenic Deep Neck Infections: A Report of Three Patients

Abstract: Background:Deep neck infections are important otolaryngologic emergencies due to serious complications and the risk of airway compromise, which can lead to mortality. Although the most common causes among pediatric patients are tonsillitis and pharyngeal infections, odontogenic infections are an important cause in adults.Case Report:We present three patients with multiple deep neck space abscess formation due to odontogenic infection. Two of them required tracheotomy due to airway compromise, and one had media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…involved fascial space both in single and multiple fascial space infections. Also the current study is in agreement İsmi et al, 16 who reported that the second and third mandibular molar teeth are important sources of deep neck infections, because their roots extend to the junction of the mylohyoid muscle with the mandibular corpus adjacent to the submandibular and parapharyngeal spaces, making the submandibular space the most commonly involved area in this type of infections. Additionally Walia et al, 17 also reported the submandibular space to be the most commonly infected space.…”
Section: Discussionsupporting
confidence: 92%
“…involved fascial space both in single and multiple fascial space infections. Also the current study is in agreement İsmi et al, 16 who reported that the second and third mandibular molar teeth are important sources of deep neck infections, because their roots extend to the junction of the mylohyoid muscle with the mandibular corpus adjacent to the submandibular and parapharyngeal spaces, making the submandibular space the most commonly involved area in this type of infections. Additionally Walia et al, 17 also reported the submandibular space to be the most commonly infected space.…”
Section: Discussionsupporting
confidence: 92%
“…In the pre antibiotic era, several studies showed that most DNI cases (70-80%) resulted from complicated tonsillopharyngeal infections, whereas nowadays, the incidence has reduced (8-16%) though in children acute upper respiratory tract infection is the commonest cause, and odontogenic infection the next common cause. 18,19 The usual presentation in infants is various types of neck abscesses as it is difficult to make out the early clinical features. 20 The next common cause in our study was foreign body especially fish bone of the upper aero digestive tract (26.32%).…”
Section: Resultsmentioning
confidence: 99%
“…Na TC do caso foi avaliado o velamento importante da região de seio maxilar a esquerda. Assim, para que não haja uma evolução do quadro clínico do paciente o tratamento prévio é essencial (Yuvaraj, 2016;Ismi et al, 2017;Uittamo et al, 2020).…”
Section: Discussionunclassified